内齿轮传动机构动力特性及可靠性的数值模拟 - 王凯; 孙秦 (Jixie chuandong)
In connection with the requirement of the gear mechanism,finite element analysis software ANSYS is used to generate the accurate numerical model for the transmission of standard internal gear.Then,the full method of ANSYS dynamic analysis is used to carry out numerical simulation of the process of gear mechanism which is driven by soft and hard startup modes,and use postprocessor of ANSYS to describe the results of the numerical analysis in graphics and curves.Finally,the reliability of the strength of the gear root is evealuated.By comparing the dynamic response and strength reliability of gear under two different way of load,the maximum level of stress could be reduced under the soft-stat mode,thus the strength reliability of gear root is improved.The analysis method has wide applicability to analyze dynamic response and strength other complex gear mechanisms.